Between Teachings and Practices: Gender Equality in Modern Islamic Boarding School Education - Rahmad Hidayat Munthe; Faisal Riza (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the practice of gender equality in modern Islamic boarding school education at Pesantren Modern Darus Sholihin, Labuhan Batu. The research focuses on how female students understand, experience, and negotiate gender equality in everyday educational practices. Using a qualitative method with a phenomenological approach, data were collected through in-depth interviews, observation, and documentation involving two informants: a female student leader and a religious teacher. The findings show that gender equality in the pesantren is understood as justice based on Islamic values rather than absolute equality. Female students are given opportunities to participate in academic, organizational, and leadership activities, although several gender-based role divisions and restrictions still exist. The study concludes that gender equality in modern pesantren is socially constructed through negotiations between Islamic teachings, institutional culture, and contemporary social changes, allowing pesantren to become a more inclusive educational space for women.